New Auditing Techniques/Audit Programs and Working Papers (Book). - Miller, Herbert E.; Boddy, F. M. (The Accounting Review, 1946)
Abstract Reviews two books "New Auditing Techniques" and "Audit Programs and Working Papers," by Maurice E. Peloubet.